Ramsay Hunt Syndrome in a Patient with Rheumatoid Arthritis after Treatment with Infliximab - Yoshio Nagayama; Naoki Matsushiro; Akihide Nampei; Hideo Hashimoto; Kenrin Shi (Case Reports in Rheumatology)
A 39-year-old female patient with rheumatoid arthritis developed Ramsay Hunt syndrome after infliximab treatment. This condition is caused by the reactivation of varicella zoster virus infection in the geniculate ganglion of facial nerve in the host’s immunosuppression. She was treated immediately with valaciclovir and hydrocortisone, and the complete recovery was achieved at 6 months after the onset. This is the first report of Ramsay Hunt syndrome as an adverse effect of infliximab in rheumatoid arthritis.